2012
DOI: 10.1007/s12010-012-9809-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Elicitation Conditions with Methyl Jasmonate and Salicylic Acid to Improve the Productivity of Withanolides in the Adventitious Root Culture of Withania somnifera (L.) Dunal

Abstract: Adventitious root cultures derived from leaf derived callus of Withania somnifera (L.) Dunal were treated with methyl jasmonate and salicylic acid independently. Biomass accumulation, culture age, elicitation period, and culture duration were optimized for higher withanolides production in the two best-responding varieties collected from Kolli hills (Eastern Ghats) and Cumbum (Western Ghats) of Tamil Nadu, India. Between the two elicitors, salicylic acid (SA) improved the production of major withanolides (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Studies have reported elicitation as a suitable strategy for enhancing secondary metabolite production in adventitious root cultures of several plants such as Valeriana amurensis (Cui et al, 2012), M. citrifolia (Baque et al, 2012b), Angelica gigas (Rhee et al, 2010) and Withania somnifera (Sivanandhan et al, 2012). Enhanced Table 2 Influence of different concentrations and combinations of plant growth regulators on biomass and plumbagin accumulation of adventitious root cultures of Plumbago rosea in MS liquid medium.…”
Section: Elicitor Treatment For Plumbagin Productionmentioning
confidence: 99%
“…Studies have reported elicitation as a suitable strategy for enhancing secondary metabolite production in adventitious root cultures of several plants such as Valeriana amurensis (Cui et al, 2012), M. citrifolia (Baque et al, 2012b), Angelica gigas (Rhee et al, 2010) and Withania somnifera (Sivanandhan et al, 2012). Enhanced Table 2 Influence of different concentrations and combinations of plant growth regulators on biomass and plumbagin accumulation of adventitious root cultures of Plumbago rosea in MS liquid medium.…”
Section: Elicitor Treatment For Plumbagin Productionmentioning
confidence: 99%
“…The elicitation process is generally regarded as the expression of defense-related genes and activating defense-related secondary metabolic pathways. Elicitation is a very complex process and depends on many factors such as elicitor concentration, growth stage of the culture at the time of elicitor addition and contact time with the elicitor [17]. In addition, the response to a particular elicitor may vary from plant to plant.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of various organic additives (L-glutamine, casein hydrolysate, adenine sulphate, coconut water and malt extract) and seaweed extracts ( Sargassum wightii and Gracilaria edulis ) were studies by Sivanandhan et al [ 13 ] on the biomass accumulation and withanolide production. Among the different organic additives supplemented in the cell In the adventitious root cultures of Withania , salicylic acid and methyl jasmonate at different concentrations and different exposure time were studied for the biomass accumulation and withanolide production and the results suggested that addition of 30-day-old adventitious root cultures with 150 μM salicylic acid for 4 h elicitor exposure period and harvesting the adventitious roots at 40 days interval resulted in the highest production of withanolides compared to the methyl jasmonate treatments [ 47 ]. In another study, Sivanandhan et al [ 17 ] reported that chitosan at 100 mg L −1 with 4 h exposure time stimulated the higher withanolides production at the end of 6 weeks of culture period when compared with different concentrations and exposure time of chitosan and aluminium chloride.…”
Section: Effect Of Elicitors On Biomass Accumulation and Withanolide mentioning
confidence: 99%